2018 Joint International EUROSOI Workshop and International Conference on Ultimate Integration on Silicon (EUROSOI-ULIS) 2018
DOI: 10.1109/ulis.2018.8354732
|View full text |Cite
|
Sign up to set email alerts
|

Random discrete dopant induced variability in negative capacitance transistors

Abstract: In this work we investigate the impact of random discrete dopants (RDD) induced statistical variability in ferroelectric negative capacitance field effect transistors (NCFETs). We couple the 3D 'atomistic' statistical device simulator GARAND with the Landau -Khalatnikov equation of the ferroelectric for this study. We find that the negative capacitance effect provided by the ferroelectric layer can lead to suppression of the RDD induced variability in the threshold voltage (Vt), OFF-current (IOFF), and ON-curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, RDF‐induced fluctuation of these parameters can also be successfully suppressed, i.e., σV th , σ SS, and σI OFF of n‐NCFET and p‐NCFET are reduced as compared to the baseline transistors in both the linear and saturated regions. Note that the σI ON of the NCFETs increases with the FE capacitor applied, but the relative standard deviations are smaller (as also demonstrated in [16]). Because I ON in NCFETs is obviously higher than in the baseline MOSFETs, it is more significant to compare the relative standard deviation than the standard deviation.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, RDF‐induced fluctuation of these parameters can also be successfully suppressed, i.e., σV th , σ SS, and σI OFF of n‐NCFET and p‐NCFET are reduced as compared to the baseline transistors in both the linear and saturated regions. Note that the σI ON of the NCFETs increases with the FE capacitor applied, but the relative standard deviations are smaller (as also demonstrated in [16]). Because I ON in NCFETs is obviously higher than in the baseline MOSFETs, it is more significant to compare the relative standard deviation than the standard deviation.…”
Section: Resultssupporting
confidence: 58%
“…Li et al [15] demonstrated that propagation delay is strongly dependent on FE damping constant, which is closely related to the FE response time. Furthermore, there also have been only a few reports concerning variability in NCFETs [16, 17] and NC‐FinFETs [1821]. The research in [16] focused only on V th , I ON , and I OFF variations due to typical current–voltage characteristics in NCFETs with the possibility of negative differential resistance [22, 23] and negative drain induced barrier lowering (DIBL) phenomena [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCFETs have been realized in various architectures, including FinFET [73] and nanowire FET [74]. In addition to the prospects of improved nominal device performance [75], NCFETs have been shown to be more immune to statistical variability compared to their conventional counterparts [76][77][78][79]. NCFETs also have shown promising circuit applications [80,81].…”
Section: Negative Capacitance Fets (Ncfet)mentioning
confidence: 99%
“…Variability induced by the statistical nature of RDF and gate LER play critical role in MOSFETs, and their impact in limiting the performance of existing CMOS technologies has been investigated comprehensively using 3D simulations in the past [6], [7]. Analysis of process induced variability in the critical dimensions of NC-FinFETs was reported earlier in [8], while the suppression of RDF induced variability in bulk NCFETs was recently analyzed [9]. In this paper we extend the work to include gate LER and its interplay with RDF.…”
Section: Introductionmentioning
confidence: 99%